Not even past : how the United States ends wars - Fitzgerald, David, 1984-; Ryan, David, 1965-; Thompson, John M., 1977- (Berghahn, 2020)
"Vietnam, Iraq, Afghanistan: Taken together, these conflicts are the key to understanding more than a half century of American military history. In addition, they have shaped, in profound ways, the culture and politics of the United States-as well as the nations in which they have been fought. This volume brings together international experts on American history and foreign affairs to assess the cumulative impact of the United States' often halting and conflicted attempts to end wars. It offers essential perspectives on the Cold War and post-9/11 eras and explores the troubling implications of the American tendency to fight wars without end"--